INTENSITAS MUZAKKI DALAM MENYALURKAN ZAKAT MELALUI LEMBAGA AMIL ZAKAT RESMI JAWA BARAT - Azmi Fasa (UIN Sunan Gunung Djati Bandung, 2020)
This study aims to knowing the factors that affect muzakki in West Java to distribute zakat through the official amil zakat institutions. In this study, data were collected through questionnaires with convinince sampling. Respondents in this study are muzakki paying zakat through several LAZ in West Java namely: Rumah Zakat, DPUDT, Rumah Amal Salman, and LAZ Bina Muda. This research uses PLS-SEM analysis tool. The results of this study indicate a significant positive effect for attitudes, subjective norms, and perceive behavioral contro to intention of muzakki in distributing zakat through official LAZ. The model's ability to explain intention variables is 90.5%. Keywords: attitude, subjective norms, perceptual behavior control, intention, muzakki, the official Amil Zakat Institute